17v+26=-42

Simple and best practice solution for 17v+26=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17v+26=-42 equation:


17v+26=-42

We simplify the equation to the form, which is simple to understand
17v+26=-42

We move all terms containing v to the left and all other terms to the right.
+17v=-42-26

We simplify left and right side of the equation.
+17v=-68

We divide both sides of the equation by 17 to get v.
v=-4

See similar equations:

| s+-12=16 | | 4*2g-3=8g-2 | | x=x^2+4x+3 | | 20-2p=4p-4 | | -48/-3= | | -3(3p+4)-2(4-11p)=3(2+4p) | | 2x^2+12x=4 | | d=1/2(3)-2 | | 7(4-3x)+3=-6(x-4)-8 | | -48/3= | | b^2-3b+4=0 | | 59-4=91 | | 8n+6-6n=34 | | 4*(3-6a)=36 | | x^2+12x-6=46 | | 15x^2-19x-10= | | 4y=-36+4x | | (2x+2)+y+7=180 | | 2(r-.5)=-2 | | 144p-309.60=50.40 | | (r-2)(r+8)=23 | | 18-7x+1=-9 | | 4f=-7 | | 6(2/5)-3= | | 63-6x=1x | | -2(.5-4s)=-3(4-3.5s) | | 2x=14+y | | -(2+7x)-6(-7-x)=36 | | -3x+4=-11 | | -11.77+11.6b=19.43+13.9b+2.5b | | 2x^2+3x+6=13 | | -7(-1)= |

Equations solver categories